Unveiling the structure and dynamics of peeling mode in quiescent high-confinement tokamak plasmas - Kensaku Kamiya (Nature Portfolio, 2021)
Unveiling the properties of edge harmonic oscillation is one of the major pursuits to understand complex systems in plasma physics. The authors present measurements at the JT-60U tokamak that show direct observations of peeling modes in quiescent high-confinement tokamak plasmas, offering insights into the “peeling nature” of both laboratory plasmas and astronomical plasmas.